Penerapan cegah stres pada ayam ras petelur : Application of stress prevention in laying chickens - Safriyanto Dako; Nibras Laya; Fahria Datau; Syukri Gubali; Sri Yeni Pateda; Syahruddin Syahruddin; Suparmin Fathan; Srisukmawati Zainudin (Fakultas Peternakan Universitas Papua, 2023)
ABSTRACT Laying breeds of chickens are sensitive to stress, which can affect growth and egg production. The aim of this service is to implement stress prevention in the laying hen business for a group of laying hen breeders in Inomata Village, Bonebolango, Gorontalo. The Active Participatory Service (PRA) model is implemented through group mentoring. Activities are carried out through preparation of mentoring activities, building agreements, consultations and scheduling in mentoring and problem inventory. Education is carried out for breeders with knowledge and skills, namely motivating breeders, providing knowledge and skills in preventing stress in laying hens. Organizing community service activities on how to prevent stress in laying hens for breeders in Inomata village can prevent stress in laying hens. Keywords: Breeder groups; Laying chickens; Stress pressure ABSTRAK Ayam ras petelur sensitif terhadap stress, sehingga dapat mempengaruhi pertumbuhan dan produksi telur. Tujuan pengabdian ini menerapkan pencegahan stress pada usaha ayam ras petelur bagi kelompok peternak ayam ras petelur di Desa Inomata, Bonebolango, Gorontalo. Model pengabdian Partisipatori Aktif (PRA) dilaksanakan melalui pendampingan kelompok. Kegiatan dilaksanakan melalui persiapan kegiatan pendampingan, membangun kesepakatan, rembuk dan penjadwalan dalam pendampingan dan Inventaris masalah. Edukasi dilakukan pada peternak dengan pengetahuan dan keterampilan yakni memotivasi peternak, pembekalan pengetahuan dan ketrampilan dalam mencegah terjadinya stress pada ayam petelur. Terselenggaranya kegiatan pengabdian tentang cara cegah stress pada ayam petelur bagi peternak didesa Inomata dapat melakukan pencegahan stress pada ayam petelur. Kata kunci: Ayam petelur; Kelompok peternak; Tekanan stress